5-aminolevulinic acid in photodynamic treatment of superficial basocellular epithelial lesions of the skin - Szymańczyk, Jacek; Domaniecki, Janusz; Tomczak, Marek; Kwaśny, Mirosław; Steć, Mirosław; Mierczyk, Zygmunt (Contemporary Oncology/Współczesna Onkologia, 1999)
Currently employed methods of treatment of cutaneous neoplasms carry the risk of functional and cosmetic postoperative defects. Photodynamic therapy seems to minimize these risks. New photosensibilizing substances (especially those applicated topically) diminish the prolonged photosensibility reaction. 5-aminolevulinic acid, the natural precursor substance in the heme biosynthesis, leads to the induction of photodynamically active photoporphyrine IX. This 2-nd generation photosensibilizing agent was employed in the treatment of 15 patients with single basocellular epitholoid skin tumours. The drug was applied topically and then the lesion was irradiated with light of 630 nm wavelength. Immediately after irradiation, oedema of the treated area appeared and persisted during the following 2-3 days. Superficial necrosis of the lesions, reduction of tumour size and formation of atrophic scar were observed during the follow-up period. The method of treatment employed was not fully successful – in only 2 patients biopsy did not reveal neoplastic cells 3 months following the initial treatment. The short period of follow-up, as well as the small number of patients do not allow to draw definite conclusions. We think however, that photodynamic method with the topical use of 5-aminolevulinic acid, as photosensibilizing agent, may be useful in diagnostics and treatment of superficially located neoplastic skin lesions.